Ageing and dementia: what do community health workers know? - Fernandes, Heloise da Costa Lima; Pavarini, Sofia Cristina Iost; Barham, Elizabeth Joan; Mendiondo, Mariza Silvana Zazzetta de; Luchesi, Bruna Moretti (Revista da Escola de Enfermagem da USP, 2010)
The objective of this qualitative study was to assess the knowledge of community health workers (CHW) with respect to aging and dementia, with the purpose of assisting the implantation of caregiving services focused on dementia, in a city in the State of São Paulo. All ethical guidelines were followed. In all, 51 CHW were evaluated. Semi-structured interviews were conducted. The data analysis was based on content analysis. In response to the question, What does elderly mean, for you?, the majority of the workers associated old age with chronologically advanced age and with negative aspects of aging, such as physical and social dependence. With respect to the concept of dementia, the majority of those interviewed defined dementia as a biological problem that affects the brain, compromising memory functions and resulting in dependency. The results demonstrate the need for an educational program for CHW, in the area of gerontology.